(untitled) (Studia theodisca, 2019)
The aim of this paper is to reconsider Peter Szondi’s readings of Friedrich Hölderlin, beginning with Versuch über das Tragische (1961) up to the Hölderlin-Studien (1967), with particular regard to the essay Der andere Pfeil. Zur Entstehungsgeschichte von Hölderlins hymnischem Spätstil. Hölderlin’s conception of «das Tragische» as outlined in Szondi’s first mentioned work will be discussed in relation to his later reading of Wie wenn am Feiertage… and of Hölderlin’s hymnic style. This will show how the poet’s idea of the tragic movement (from the unity of the human and the Divine to their separation) becomes Szondi’s gateway to the understanding of Hölderlin’s late poetry, his translations, and his poetics. Just like Oedipus, whom the Gods punish for his nefas, the poet is struck in Wie wenn am Feiertage… by the “other arrow” and condemned to “divine infidelity” since he cannot stand bareheaded before the Divine and celebrate it in song.